Sementes de braquiária submetidas ao contato com adubo químico - Avelino, Anne Caroline Dallabrida (2016)
In integrated crop-livestock system, it highlights the sowing of grain crops with forage in intercropping, in which the forage seed can be sown simultaneously with the grain-producing crop, mixing and distributing it with the fertilizer. Goal was to evaluate the effect of contact time on the physiological quality of Brachiaria seed with the formulated 05-25-15 (N-P2O5-K2O), commonly used in corn seeding. Two experiments were conducted in a completely randomized design, with five treatments and four replications. Treatments consisted of 0, 24, 48, 72 and 96 contact hours of Brachiaria brizantha cv. Marandu and Brachiaria ruziziensis cv. Kennedy seeds with formulated 05-25-15. After contact time, seeds were separated from fertilizers, quantified for water content and submitted for the tests: first germination count, germination, tetrazolium (viability), electrical conductivity, accelerated aging, first emergency count in sand, sand emergency, emergency speed index, length of larger root and shoot, and seedling dry mass. The results were submitted to analysis of variance and regression at 5% probability. Regarding Brachiaria brizantha cv. Marandu seeds, effect of contact time was observed for variables: germination, first emergence count, emergence speed index and electrical conductivity. Comparing the treatment of 96 hours of contact with the absence of contact, the results indicate a negative linear effect of contact time, with a reduction of 46.48; 24.54; and 21.89% in germination, first emergency count and emergency speed index, respectively. There was a positive linear effect of contact time with an increase of 110.38% in electrical conductivity. Considering the Brachiaria ruziziensis cv. Kennedy seeds, no effect of contact time was observed for variables: electrical conductivity, accelerated aging and viability. There was a positive linear effect of contact time on the electrical conductivity and a quadratic effect on accelerated aging. An increase of 23.93% was observed at the electrical conductivity values when comparing the treatment of 96 hours of contact with the absence of contact and a minimum of 66.50% of germination when reaching 42 hours in accelerated aging. Results obtained for both grasses are related to the fertilizer characteristics, such as saline power and obtaining by acid pathway. Based on the minimum germination of 60% required for commercialization, it is recommended the immediate sowing of Brachiaria brizantha cv. Marandu seeds and sowing up to 96 hours of Brachiaria ruziziensis cv. Kennedy, after mixing with fertilizer.